Generalized product-sum variogram models of the data of the Center of Marine Research - Krūminienė, Ingrida; Dučinskas, Kęstutis (Lietuvos matematikos rinkinys, 2004)
Environmental data usually depends on both spatial and temporal components. Therefore, it is essential to have statistical models to describe how the data vary across space and time. Structural analysis begins with estimating the space-time covariance or variogram. In this paper a generalised product-sum variogram models has been fitted to the data of the Center of Marine Research by making use of Gstat software.
Keywords: spatial-temporal models; covariance; variogram; product-sum models